Peranan Departemen IT dan Dukungan Tenaga Support serta Pemahaman Karyawan Terhadap Standar Operasional Prosedur Akan Meningkatkan Kualitas Layanan IT - Fried Sinlae; R Wisnu Prio Pamungkas; Nani Sudiarti (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
How big is the role of the IT department and support? Support staff and employee understanding in improving IT services, which in this research is PT. XYZ, especially in raising the value of IT performance. The research method used is a quantitative method with a cause and effect relationship approach with a sample of respondents from 3 independent variables and 1 dependent variable. The sampling technique uses proportionate stratified random sampling so that it can be used proportionally according to the group or equivalent of the population or respondents. Analysis of the role of the IT Department and the support of Support Personnel as well as employee understanding of Standard Operating Procedures can improve the quality of IT services and have an impact on improving IT performance. Research on the role of 3 (three) independent variables as a discussion is still rarely discussed in Standard Operating Procedures. So it is necessary to consider whether employees' understanding of the existence of IT services can improve the quality of IT services themselves and will have an impact on increasing the value of IT performance.